2015
DOI: 10.1182/blood-2014-06-577783
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous and arterial thrombotic events in patients diagnosed with superficial vein thrombosis: a nationwide cohort study

Abstract: Key Points• In the 3 months after isolated SVT, the risk of a deep venous event or pulmonary embolism is 3.4%.• This risk remains fivefold increased more than 5 years after the superficial event.Recently, it has become apparent that superficial vein thrombosis (SVT) can have serious complications. However, the magnitude of the risk of subsequent deep venous and arterial thrombotic events remains unknown. We examined this in a nationwide population-based setting during a period when SVT was not treated routinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 32 publications
(41 reference statements)
3
45
0
3
Order By: Relevance
“…Although it has been traditionally considered a relatively benign disease, a number of recent studies have suggested a not uncommon concomitant presence of DVT and/or PE in these patients [5,[13][14][15] and a non-negligible risk of recurrence at follow up [16,7], questioning the benign nature of this disease. It is important to diagnose DVT when present in patients with SVT because patients with an isolated SVT and patients with a concomitant major thromboembolic disease may have a different clinical history and, according to recent guidelines [17], a less aggressive therapy with six weeks of prophylactic doses of fondaparinux appear to be effective in preventing major thromboembolic complication and SVT recurrence in the former group [18] whereas at least three months of therapeutic doses of antithrombotic therapy are necessary in the latter group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been traditionally considered a relatively benign disease, a number of recent studies have suggested a not uncommon concomitant presence of DVT and/or PE in these patients [5,[13][14][15] and a non-negligible risk of recurrence at follow up [16,7], questioning the benign nature of this disease. It is important to diagnose DVT when present in patients with SVT because patients with an isolated SVT and patients with a concomitant major thromboembolic disease may have a different clinical history and, according to recent guidelines [17], a less aggressive therapy with six weeks of prophylactic doses of fondaparinux appear to be effective in preventing major thromboembolic complication and SVT recurrence in the former group [18] whereas at least three months of therapeutic doses of antithrombotic therapy are necessary in the latter group.…”
Section: Discussionmentioning
confidence: 99%
“…It has become recently more clear, however, that SVT may be a manifestation of a systemic tendency to thrombosis, with a non-negligible risk of recurrence or concomitant DVT or PE at the Thrombosis Research xxx (2015) xxx-xxx time of SVT diagnosis [7]. Unfortunately, available data on this association are not conclusive, ranging between 6% and 36% for concomitant DVT and up to 33% for PE [1,8].…”
Section: Introductionmentioning
confidence: 96%
“…120 Other risk factors for incident VTE include central vein catheterization or transvenous pacemaker placement, prior superficial vein thrombosis, urinary tract infection, increased baseline plasma fibrin d -dimer, and family history of VTE, whereas patients with chronic liver disease have a reduced risk of VTE. 121127 Compared with residents in the community, hospitalized patients have >100-fold increased incidence of VTE. 128 Hospitalization and nursing-home residence together account for almost 60% of incident VTE events in the community.…”
Section: Risk Factors For Incident Vtementioning
confidence: 99%
“…High mortality is associated with a delayed diagnosis of acute PE [3]. Recent studies have indicated that the predisposing factors for PE include numerous underlying diseases such as obstructive airway disease (causing asthma [4] and chronic obstructive pulmonary disease [COPD] [5]), atherosclerosis [6] (causing hypertension, diabetes [7], and stroke), heart failure [8] and cancer [9]. …”
Section: Introductionmentioning
confidence: 99%